Mechanical failures of Two-Dimensional materials on polymer substrates - Chae, Kwanbyung; Nguyen, Van Tu; Lee, Sangryun; Phung, Thi Quynh; Sim, Yumin; Seong, Maeng Je; Lee, Sangwoon; Ahn, Yeong Hwan; Lee, Soonil; Ryu, Seunghwa; Park, Ji Yong (Applied Surface Science, 2022)
The mechanical stability and failures of two-dimensional (2D) materials on the compliant polymer substrates under biaxial strain are investigated. As the polymer substrate swells, the fracture of the system is initiated with the crack-formation in 2D materials (graphene and MoS2 flakes), which propagates deep into the substrates. According to the fracture theory, the generation of deep cracks in such a system (thin hard material on a compliant substrate) is expected to be a universal behavior due to a large mismatch in the elastic moduli between the film and the substrate. The properties of crack formation in systems with varying crystallinity and size of 2D materials are also investigated. The present results provide important insights into what to consider for mechanical stability in designing flexible devices based on 2D materials.
Keywords: Biaxial strains; Compliant substrates; Cristallinity; Mechanical failures; Polymer substrate; Property; Thin hard materials; Two-dimensional; Two-dimensional materials; Universal behaviors; Crack; Fracture; Graphene; Molybdenum disulfide; Polymer; Strain